Vocational College's Students Preferences on Practical Teaching Methods for Electronic Subject - Nasir, Ahmad Nabil Md; Ahmad, Adnan; Udin, Amirmudin; Abd Wahid, Nur Husna; Suhairom, Nornazira (Journal of Technical Education and Training, 2020)
Practical teaching approaches in the classroom or workshop plays an important role in teaching and learning process especially for hands-on subjects. The practical teaching methods that teach according to the ability of the students can give them better understanding in a specific subject. Hence, this paper will look at the practical teaching methods that are preferred by the Malaysian Vocational College's student for electronic subject. Quantitative studies approach has been employed which adopted the survey design using questionnaires as the instrument for data collection.  The respondents of this research were selected from 306 students in 58 Vocational Colleges which offer Electrical and Electronics Engineering Technology courses. Descriptive analysis has been carried out for this study and the data such as mean, standard deviation and ranking were analysed. The result showed that student preferred teaching method that provide easy understanding on the hands-on topic based on the Needham 5 phase constructivism model.  In the beginning phase, the student preferred demonstration, practical activities use video clips, diagram and hand note.  However in Idea Generation, Strengthening of Ideas and Applying Ideas phase, they preferred the teaching that focusing on group rather than individual such as practical work, discussion, mind map and invention. In the reflection phase, the students most preferred using question and answer openly in class and small group. Based on this study, the findings will help the teachers to use the specific teaching methods that provide easy understanding for the students' especially for the hands-on subject.